The role of PIK3CA mutations in the development of breast cancer (a literature review) - A. O. Pryvalova; I. O. Vynnychenko; V. Yu. Harbuzova; O. I. Vynnychenko; Yu. V. Moskalenko (Zaporožskij Medicinskij Žurnal)
Today, breast cancer occupies a leading position in the structure of morbidity and mortality among women in Ukraineand and throughout the world. Late diagnosis of the disease adversely affects the prognosis. Since this pathology is characterized by a wide range of gene mutations, the relationship between the molecular genetic characteristics of a tumor and the prognostic and clinical characteristics of breast cancer is an extremely important issue. The PI3K/Akt signaling cascade is one of the key intracellular signaling pathways associated with the control of cell proliferation and regulation of potential oncogene protein kinase B/Akt functions. It can suppress apoptosis in different types of cancer, contributing to tumor cells survival. Also, mutations and amplification of the PI3K/Akt cascade components cause malignant cell transformation of various origin. The PIK3CA gene is one of the oncogenes, somatic mutations in which play an important role in the pathogenesis and progression of breast cancer. It encodes p110-α, the catalytic subunit of phosphatidylinositol-3-kinase-α. The most frequent mutation in PIK3CA gene is H1047R.